Trends, geographical variation and factors associated with the use of anti-VEGF intravitreal injections in Portugal (2013-2018) - Rocha, João Victor (2022)
Funding Information: Funding This analysis was funded by Novartis Farma, Produtos Farmacêuticos SA (no grant number). Publisher Copyright: © 2022 Georg Thieme Verlag. All rights reserved.